Can Osteoprotegerin be a Target of Therapy in Type 2 Diabetes Mellitus? - Berezin, A. E.; Березін, Олександр Євгенійович (My University, 2016)
Osteoprotegerin (OPG) is a soluble member of the tumor necrosis factor receptor superfamily, which exhibits the close link to Cardiovascular (CV) disease in Type 2 Diabetes Mellitus (T2DM). Recent clinical studies have been shown that elevated OPG might be a marker of vascular calcification / remodeling and CV events and CV mortality in T2DM without known CV disease. However, it remains unclear whether OPG would be a target for therapy of diabetics with antidiabetic drugs and statins. The aim of the mini review: to summarize knowledge with respect to OPG utilization as predictor of CV adverse effects and as a target of therapy in T2DM. The review is discussed the evidence regarding possibility to prevent microvascular and macrovascular complications in diabetics through control of OPG level as a target in therapy. Although there are not irresistible findings that the post-treatment OPG level in diabetics and CV events might be related, possibility to use OPG for risk stratification of vascular remodeling / ectopic calcification and CV-related mortality in T2DM appears to be attractive. The future investigations are needed to explain whether serum OPG would be informative for biomarker-guided therapy in T2DM individuals.
Keywords: Diabetes mellitus; Osteoprotegerin; Cardiovascular events; Target therapy; Prediction